Analysis of Value-Added Activities and Non-Value-Added Activities in the Production Process of Car Body Stands Using the Manufacturing Cycle Effectiveness (MCE) Method - Lita Silvianti Rosyadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2026)
PT. XXX is a manufacturing fabrication company whose production process still involves non-value-added activities, resulting in a mismatch between planned and actual timelines, including a three-day delay in the production of the Car Body Stand. This study aims to identify value-added and non-value-added activities, calculate cycle time, and analyze Manufacturing Cycle Effectiveness (MCE) by comparing predicted and actual timelines, as well as to propose improvements to enhance production performance. The findings show that total value-added activities reach 480.5 hours, while non-value-added activities account for 41 hours. The predicted cycle time is 467 hours, whereas the actual cycle time extends to 551.5 hours. The MCE is 88.9% under predicted conditions and 85.8% in actual conditions. After implementing the proposed improvements, non-value-added activities decrease to 27 hours, and the cycle time improves to 523.5 hours, leading to an increased MCE of 90.4%. Overall, these results suggest that reducing non-value-added activities can effectively improve production efficiency and reduce delays.